From the Traditional Classroom to The Metaverses: A Literature Review - Saza Bustos, Lina; Escobar Sarria, Ruth Dary; Millán Rojas, Edwin Eduardo; Pinto Lopera, Jesús Emilio (Academia y Virtualidad, 2024)
This work aims to interpret the pedagogical and technological elements in the literature associated with using emerging technologies in the teaching process. For this reason, exploratory research was carried out with a qualitative approach, identifying through a search by categories and subcategories in bibliographic databases. In the same way, four research questions were used, which yielded 68 articles that contributed to the development of this. The pedagogical elements of the traditional classroom were found to be mantained over the years, and some technological elements have been incorporated. So, significant advances in the use of information and communication technologies are evident. Likewise, essential changes are reflected in society and the educational system without the fundamental transformations demanded by 21st-century education. In addition, events, limitations, barriers, changes, needs, system actors, progress, application areas, as well as positive aspects related to the application of these innovative tools (augmented reality, virtual reality, mixed reality, and 3D video games) that favor work in the classroom and the teaching process. Finally, the possibility of permanence in the future is also evident, given its captivating power with the younger population, destined to become a permissible alternative aimed at the educational scenario from the transformation of the traditional classroom to the digital, in an innovative way through new technologies.